PENGARUH MEDIA KOPIN (KOTAK PINTAR) TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK PERTIWI 3 PADANG - Yunisa, Vira; Rakimahwati; Suryana, Dadan; Saridewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Students' struggles with letter recognition when they are five or six years old in kindergarten serve as the impetus for this study. Many kids still have trouble learning to recognize individual letters, distinguish between them, and associate them with their sounds, so clearly this is a problem. Furthermore, engaging and diverse learning materials are still not enough to support the continuous learning process. Finding out how using kopin media (smart box) affects letter recognition in 5-6 year olds in Pertiwi 3 Kindergarten Padang is the main goal of this study. This research makes use of a quantitative approach with a quasi-experimental methodology. All of the students of Pertiwi 3 Kindergarten Padang make up the study's population. The sample for this study consists of 26 students from B1 and B2 courses. The data was gathered through careful observation, as well as performance testing and documentation. Hypothesis testing, homogeneity tests, and normality tests were used to analyze the data. Based on the findings of the hypothesis test, the two-tailed sig value is 0.000 < 0.05. According to the study's findings, Ha is accepted and H0 is denied. Children at Pertiwi 3 Kindergarten, Padang, Indonesia, who are five or six years old, demonstrate a remarkable improvement in their letter recognition skills after using the Kopin media (smart box).